IMPLEMENTASI TEKNIK KRIPTOGRAFI VISUAL PADA CITRA KEABUAN DAN BERWARNA UNTUK OTENTIKASI PENGGUNA PADA TRANSAKSI ONLINE - Stephanie Imelda Pella; Hendro FJ Lami (Jurnal Media Elektro, 2021)
Visual cryptography (VC) technique encodes an image into two or more shares that appear random in human eyes. In the decryption section, the pixels in the shared images are combined to obtain the information contained in the original image. This study applies visual cryptographic techniques to graysle and color images for user authentication in online transactions using the VC2,2 scheme. The server computer encodes the CAPTCHA image into two shared images that are sent to the user through different channels or applications. To authenticate himself, the user performs an XOR operation on both share images, identifies the information contained in the CAPTCHA and sends it to the server. In encryption test, histogram of the share image has a different pattern from the original image. The description test shows the decrypted image in this study visually has a better quality than the binary image has better quality than binary images.